Pkm Edukasi Personal Hygien Pada Balita di TK ABA 2 - Nani Jahriani; Maryaningsih Maryaningsih; Yeni Yeni Vera; Sulaiman Sulaiman (Insight Power (Kekuatan Wawasan), 2022)
Personal hygiene is an effort made by individuals to maintain personal hygiene to avoid disease. In personal hygiene, teeth and mouth need special and good attention according to predetermined procedures. It is very important to pay attention to the teeth and mouth, otherwise, there will be infection and damage to the teeth. Tooth decay in children is also the number one dental problem that occurs among preschoolers. The service is carried out for 1 day, the location of the implementation is in ABA 2 Kindergarten Education, East Kisaran, Asahan Regency, during which time what has been provided by the Kindergarten runs effectively and efficiently. During the service activities, the kindergarten children were enthusiastic and felt happy, and able to give positive results when asked questions. Most of the children were enthusiastic and cooperative in participating in this activity. After completing this service, the toddlers with the help of their parents are expected to be able to apply it in their daily lives. Keywords: Toddler health, personal hygiene